The net worth trap: investment and output dynamics in the presence of financing constraints - Jukka Isohätälä; Alistair Milne; Donald Robertson (Bank of Finland, 2014)
We study the impact of financing constraints on investment and output dynamics, in a continuous time setting with output a linear function of capital. Decline of net worth reduces investment and, if firms can rent capital to unconstrained outside investors, can create a 'net worth trap' with both investment and output falling below normal levels for long time periods. We provide a detailed account of our model solution and discuss both the economic intuition underpinning our results and the implications for macroeconomic modeling.
URN:NBN:fi:bof-201411193263
Keywords: E44; 330; cash flow management; corporate prudential risk; financial accelerator; financial distress; induced risk aversion; liquidity constraints; liquidity risk; macroeconomic propagation; multiperiod financial management; non-linear macroeconomic modelling; Tobin's q; precautionary savings